The Impact of Adsorption Property Modification by Crosslinkers on Graphene Oxide Membrane Separation Performance - Ayala Claveria, Martin (2024)
The health risks associated with the presence of heavy metals in drinking water can be severe. To address this issue, membrane separation technology is one of the consolidated alternatives. Inorganic, porous membranes were found in applications where low energy consumption is highly desirable. The selectivity of these membranes is attained by functionalisation. Graphene oxide functionalised membrane technology is promising for removing heavy metal ions. This work summarises, discusses and presents the relationship between adsorption and overall membrane separation process performance for heavy metal ions removal from wastewater when a graphene oxide-functionalised membrane is used. The separation performance depends on the hydrophobic interactions of the membrane and the solute. The electrostatic interaction between the negatively charged membrane surface and positively charged metal ions facilitates the adsorption, leading to the rejection of these metal ions. The influences of the chemical nature of the modifiers of graphene oxide layers are highlighted.